Testing and rating non-ducted air conditioners in Malaysia: The applicability of ISO standard 5151 - Mahlia, T.M.I.; Masjuki, Haji Hassan; Choudhury, I.A.; Saidur, Rahman (ACTA Press, 2002)
Air conditioners are one of the major energy-consuming appliances in the Malaysian domestic sector. According to a load survey, air conditioners account for around 8.3 of the total residential electricity consumption in Malaysia. To reduce the energy consumption in this sector, Malaysia Energy Center is considering implementing minimum energy efficiency standards for room air conditioners sometime in the coming year. The first step towards adopting energy efficiency standards is to create a test procedure for rating and testing this appliance. An energy test procedure is the technical foundation for all energy efficiency standards, energy labels, and other related programs. As room air conditioners are a climate-dependent appliance, the climatic condition for a particular country or region is an important determinant in developing the test conditions. Therefore, before setting the test conditions, the requirements for a specific country and region must be clarified. This article is an analysis of the applicability of ISO 5151 nonducted air conditioner test conditions, based on the climatic conditions in Malaysia. International adoption of ISO 5151 by several countries is also discussed. There is a trend towards international harmonization of appliance test standards; this work can be considered as support to that end.